Risk Factors and Prevalence of Urinary Tract Infection among Pregnant Women Attending Antenatal Care at Wachemo University Comprehensive Specialized Hospital - Elias Ezo MSc; Hirut Binora MSc; Fraol Solomon BSc; Asnakech Zekiwos MSc; Taye Mezgebu MSc; Senteyehu Admasu MSc; Bethelhem Birhanu MSc (SAGE Publishing, 2024)
Background Urinary tract infection is the single most common bacterial infection of mankind. Objective To assess the risk factors and prevalence of Urinary tract infection among pregnant women attending antenatal care at Wachemo University Comprehensive Specialized Hospital, Central Ethiopia, 2023. Methods An institutional-based cross-sectional study design was conducted from 2 October to 29 December 2023. The total sample size was 405 and a systematic random sampling technique was used. Data were entered using the Epi-data 3.1 version and exported to SPSS 25 for analysis. Multicollinearity was checked. The goodness of fit test was done using the Hosmer-Lemeshow goodness of fit test. Binary logistic regression analysis was done, and variables with a p -value of <0.25 in the bivariable analysis were taken into the multivariable analysis. Statistical significance was declared at a p -value of <0.05 with an adjusted odds ratio and 95% confidence interval. Result The prevalence of urinary tract infection was 40.7% with 95%CI [36.5-45.2]. Rural resident [AOR: 2.32, 95% CI: 1.36-3.96], educational status of husband no formal education [AOR: 3.38, 95% CI: 1.24-9.21], educational status of husband primary level [AOR: 2.94, 95% CI: 1.06-8.18], having vaginal bleeding [AOR: 3.89, 95%CI: 1.78-8.47], having female genital mutation [AOR: 2.98, 95%CI: 1.83-4.84], itchiness around genitalia [AOR: 3.82, 95%CI: 1.14-12.82], and using water for cleaning after defecation [AOR: 0.46, 95%CI: 0.22-0.97] were significantly associated. Conclusion Four in ten pregnant women attending antenatal care had urinary tract infections. Residence, educational status of the husband, vaginal bleeding, female genital mutation, itchiness around genitalia, and mode of cleaning after defecation were significantly associated. Therefore, creating awareness for rural women, improving the educational status of husbands`, treatment of vaginal bleeding, avoiding female genital mutation, screening and treating itchiness around genitalia, and using water for cleaning after defecation might reduce the burden.